Who Benefits Most from University Education in Switzerland? - Lionel Perini (Swiss Journal of Economics and Statistics, 2014)
Recent literature on private returns to education considers diversity in the population, heterogeneity in wage gains and self-selection into schooling. This research addresses these issues by analyzing to what extent returns associated with completing a university degree in Switzerland depend on the propensity to attend and complete this degree. Using data from the Swiss Household Panel and propensity score matching models, I find that low propensity men - after controlling for labor market variables - benefit most from a university degree while returns for women are rather homogenous along the propensity score distribution. This finding suggests that completing university increases more the earning capability of men with disadvantaged family backgrounds than that of men with more favorable background, refuting the hypothesis of comparative advantage. An auxiliary analysis focusing on the relationship between returns to education and inherent ability within a quantile regression framework leads to similar conclusions.
Keywords: I21; I24; J31; 330; Return to education; heterogeneity; propensity score matching